Panca Wali Krama 2019; through fire of Mount Agung Eruption to Overloaded Morgue crisis - Ida Ayu Adi Trisnawathi (Bali Tourism Board, 2019)
Balinese people hold Yadnya ceremony Panca Wali Krama every ten years. Panca means Five, represents five elements that compose the universe Panca Maha Bhuta, while Bali or Wali means offering or ceremony. In this year, the ritual was considered exceptional due to it took place twice, the first in Lempuyang Luhur Temple and the second in the largest temple in Bali, Besakih Temple. Hindu communities from all regions in Bali came to participate in the event, as their symbol of faith toward the God Almighty. This ten-year event took place for more than twenty days in Lempuyang Luhur and thirty-seven days in Besakih temple. While Panca Wali Krama was taking place at Besakih, Mount Agung has been reported experiencing several hiccups on 9, 15 and 21 March 2019. Despite the eruption, the communities kept doing their prayer and service at the temple located on the slope of the volcano. Meanwhile, another crisis was faced by hospitals on the island, due to an announcement from the official to ban Ngaben ceremony until the Yadnya is over. As a result, Mortuary in several hospitals was reported overloaded. The official and Government hastily response to the overloaded problem, since according to Balinese Hindu believe, keeping the dead body stranded was considered defiling the area.